Looking for the man's and poet's fate - Notes in the margin of the late work by Vladimir Vokolek - Lukas, Martin (Bohemica Olomucensia, 2014)
The article deals with the late work of Czech poet Vladimir Vokolek who may be considered a deeply religious and philosophical author. Major themes of his late poetry are the human condition in the modern world, the meaning of world's history, or the poet's struggle to render reality. These are discussed with respect to philosophical and religious notions or images found in the poems.
Keywords: Vladimir Vokolek